A method for preparing ultrafine centrifugal glass wool
The ultrafine glass fibers are processed through specific raw materials and preparation processes, and the problems of poor wear resistance and insufficient toughness of glass fiber cotton in the prior art are solved, achieving higher wear resistance and toughness, while maintaining sound insulation and corrosion resistance.
Patent Information
- Application Number
- CN202411922220.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-25
AI Technical Summary
Existing ultrafine centrifugal fiberglass cotton has problems such as poor wear resistance, insufficient toughness, and fragments or fibers affecting air quality and human health.
By selecting specific raw materials and preparation processes, including melting the glass raw materials into glass slurry, throwing them into ultrafine glass fibers through a fiber-forming machine, treating the fibers with acid liquid and 3-aminopropyltriethoxysilane, forming a pretreatment liquid, spraying saturated lime water on the surface of the fibers, and finally bonding to the fibers with a modified polymer as a binder.
It improves the wear resistance and toughness of ultrafine centrifugal glass wool, reduces the generation of fragments and fibers, and maintains sound insulation and corrosion resistance.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of glass wool, and in particular to a method for preparing ultrafine centrifugal glass wool. Background Art
[0002] Ultrafine glass fiber wool is a glass fiber with a diameter of microns. It has excellent properties such as light material, high temperature resistance, corrosion resistance, heat preservation, and sound insulation. It is widely used in high-tech fields such as military, aerospace, transportation, and construction. It is an indispensable sound insulation and heat insulation functional material for high-end vehicles such as aircraft, rockets, and aircraft carriers. It is also an important indicator of the development level of a country's glass fiber industry.
[0003] There are four main preparation technologies for ultra-fine glass fiber wool: centrifugal blowing technology, flame blowing technology, air-laid technology, and wet-laid felt technology. Among them, air-laid technology uses the principle of dynamics to disperse short fibers under the action of aerodynamic force to make dry-laid glass fiber wool felt; wet-laid felt technology uses the principle of papermaking technology to evenly disperse fibers and water in a certain proportion to form a suspension, and then dry it into a net; the glass fiber wool felts prepared by these two methods generally have larger diameters and bulk densities, complex structures, and by-products produced during the production process pollute the environment. Centrifugal blowing technology can efficiently prepare a large amount of glass wool by fiberizing molten glass through a high-speed rotating centrifugal blowing device.
[0004] However, limited by the selection of raw materials and the influence of the preparation method, the existing ultrafine centrifugal glass fiber wool still has problems such as poor wear resistance, insufficient toughness, and fragments or fibers that affect air quality and human health. Summary of the invention
[0005] The present application aims to overcome at least one of the defects of the prior art and provide a method for preparing ultrafine centrifugal glass wool. By selecting specific raw materials and preparing processes, the ultrafine centrifugal glass wool produced can further improve the wear resistance and toughness while maintaining the sound insulation and corrosion resistance, and reduce the generation of ultrafine glass wool fragments and fibers.
[0006] In the first aspect, the present application provides a method for preparing ultrafine centrifugal glass wool, which is achieved by the following technical solutions:
[0007] A method for preparing ultrafine centrifugal glass wool comprises the following steps:
[0008] (1) Put the glass raw materials into a high-temperature kiln at 1400-1600℃ and melt them into glass slurry;
[0009] (2) The molten slurry enters the fiberizing machine and is thrown into ultra-fine glass fibers through the small holes on the drum;
[0010] (3) mixing an acid solution and 3-aminopropyltriethoxysilane to form a pretreatment solution; immersing the ultrafine glass fiber in the pretreatment solution, subjecting the glass fiber to ultrasonic treatment for 5-10 minutes to fully immerse the glass fiber, and then spraying saturated lime water on the surface of the glass fiber to obtain the pretreated glass fiber;
[0011] (4) uniformly mixing the binder with the low-viscosity solvent and the additive, and spraying the mixture evenly onto the surface of the pretreated glass fiber to bond the glass fiber into shape;
[0012] (5) Send the bonded glass fiber into a curing furnace for heating to solidify the binder and solidify the fiber into shape;
[0013] Wherein, the acid solution in step (3) is prepared by mixing hydrochloric acid and hydrofluoric acid in a weight ratio of (2-3):1;
[0014] The adhesive in step (4) is prepared by mixing modified polymethyl methacrylate resin, modified vinyl acetate resin and epoxy resin in a weight ratio of (3-5):1:(2-3);
[0015] Step (1) The glass raw material is composed of the following raw materials in parts by weight: 55-60 parts of silicon dioxide, 2-3 parts of titanium nitride, 1-2 parts of aluminum oxide, 3-5 parts of calcium oxide, 4-6 parts of boron oxide, 2-3 parts of magnesium oxide, 2-5 parts of sodium oxide, 3-5 parts of lithium oxide, 2-3 parts of barium oxide, 2-3 parts of scandium oxide, and 2-3 parts of manganese oxide;
[0016] In step (4), the weight ratio of the binder to the low-viscosity solvent and the auxiliary agent is 1:(2-5):(1-2).
[0017] According to the method for manufacturing ultrafine centrifugal glass wool of the embodiment of the present application, there are at least the following beneficial effects:
[0018] The ultrafine glass fibers of the present application have excellent dispersibility and can form a strong hydrogen bond network with epoxy resin, modified polymethyl methacrylate resin, and modified vinyl acetate resin, thereby improving the bonding strength of the ultrafine centrifugal glass wool. In the present application, the glass fiber is first treated with an acid solution. The hydrochloric acid can undergo a replacement reaction with the metal oxygen ions on the surface of the ultrafine glass fiber, which helps to remove the oxides and other impurities on the surface, and at the same time hydroxylates the fiber surface to increase the number of active groups. The hydrofluoric acid treatment can make the surface of the ultrafine glass fiber rougher, increase the surface area and the number of active groups, thereby making the adhesion between the ultrafine glass fiber and the epoxy resin, modified polymethyl methacrylate resin, and modified vinyl acetate resin matrix tighter; 3-aminopropyltriethoxysilane can react with the glass fiber and the epoxy resin, modified polymethyl methacrylate resin, and modified vinyl acetate resin matrix, respectively, so that a covalent bond connection similar to a bridge can be formed between the glass fiber and the epoxy resin, modified polymethyl methacrylate resin, and modified vinyl acetate resin matrix, thereby improving the internal bonding stability of the ultrafine centrifugal glass wool.
[0019] The present application adds saturated lime water to react with residual acid, thereby neutralizing the residual acid on the surface of the glass fiber, preventing the residual acid from continuing to corrode and destroy the internal structure of the glass fiber, and ensuring the toughness of the glass fiber; utilizing the low solubility of calcium hydroxide, it is convenient to control the alkalinity and avoid excessive residual alkali; after the glass fiber is pretreated, the small amount of residual alkali solution can react with carbon dioxide in the air to generate calcium carbonate. The small amount of calcium carbonate generated has a tiny particle size and will be wrapped on the surface of the glass fiber, preventing the continuous corrosion of the glass fiber and improving the toughness of the glass fiber.
[0020] The aluminum oxide in the present application can reduce the crystallization tendency and crystallization speed of glass, and help to enhance the heat resistance and mechanical strength of the material; calcium oxide acts as a flux and stabilizer in glass fiber wool, which helps to reduce the melting temperature of glass and improve the durability of glass; boron oxide helps to improve the heat resistance and chemical stability of glass fiber wool, and also helps to reduce the melting temperature of glass; magnesium oxide can increase the forming temperature range of glass, adjust the glass material properties, and help to improve the toughness and impact resistance of the material; lithium oxide can react with silicon dioxide at a lower temperature to form silicate, thereby significantly reducing the viscosity of glass, helping to improve the melting efficiency in the manufacturing process of glass fiber, and helping to form a more uniform and dense fiber structure, thereby improving the overall wear resistance and toughness; scandium oxide can increase the hardness and stability of glass fiber, thereby enhancing the impact resistance and durability of glass fiber, extending its service life, and improving the thermal stability, chemical stability and corrosion resistance of glass fiber; manganese oxide interacts with other components to improve the mechanical strength of ultrafine glass fiber wool, making it tougher and more durable.
[0021] The titanium nitride in the present application has a high melting point and high hardness, and will not melt in the glass slurry. The addition of titanium nitride can optimize the microstructure of the glass fiber. During the melting process, the titanium nitride particles will be distributed in the glass slurry, and after being thrown out, they will form a dense microstructure with the glass slurry, thereby improving the density and strength of the glass fiber. When subjected to external force, the titanium nitride particles can bear part of the load, thereby improving the overall mechanical properties of the glass fiber.
[0022] In step (2) of the present application, the fiber can be fully impregnated by ultrasonic treatment to ensure that 3-aminopropyltriethoxysilane is evenly distributed on the surface of the glass fiber; the duration of the ultrasonic treatment has a great influence on the glass fiber. If the treatment time is too short, the surface of the glass fiber cannot be fully reacted. If the ultrasonic treatment time is too long, the interior of the glass fiber is easily corroded, affecting the structural stability of the glass fiber and causing a decrease in toughness.
[0023] The low-viscosity solvent in step (4) of the present application can reduce the viscosity of the resin matrix in the adhesive, ensure the uniformity of resin spraying and process stability, and facilitate uniform spraying and dispersion on the surface of the ultrafine glass fiber.
[0024] According to some embodiments of the present application, the surface of the titanium nitride is plated with a nickel layer. The nickel layer can increase the affinity of titanium nitride, improve the wettability of glass slurry to titanium nitride, and help improve the distribution uniformity of titanium nitride particles.
[0025] According to some embodiments of the present application, the average particle size of the titanium nitride is 500-1000 nm. This particle size can better balance the wear resistance and powder fluidity of the glass fiber, and is more conducive to improving the mechanical properties of the glass fiber.
[0026] According to some embodiments of the present application, the solid content of the epoxy resin is 85-95%, for example, the solid content of the epoxy resin is 85% or 90%.
[0027] According to some embodiments of the present application, the epoxy resin contains an active monomer with an amine group. The amine group can react chemically with a variety of functional groups to form a chemical bond, thereby enhancing the bonding force between the binder and the glass fiber. This chemical bonding is stronger than physical adsorption, thereby improving the overall strength and stability of the glass fiber wool, while improving the high temperature resistance and corrosion resistance of the binder.
[0028] According to some embodiments of the present application, the preparation method of the modified polymethyl methacrylate resin includes:
[0029] 40-50 parts of polymethyl methacrylate resin, 0.4-0.6 parts of dicumyl peroxide and 1-2 parts of trihydroxypropane triacrylate are mixed uniformly in a high-speed mixer according to weight parts, added into a torque rheometer with a rotation speed of 60 r / min, and reacted at 165° C. for 2-3 hours to obtain modified polymethyl methacrylate resin.
[0030] By modifying the polymethyl methacrylate resin, trimethylolpropane triacrylate can be grafted into the molecular chain structure of polymethyl methacrylate. Through the participation of multiple double bonds in the same trimethylolpropane triacrylate molecule in the reaction, polymethyl methacrylate forms a cross-linked network structure, and the molecular weight distribution of polymethyl methacrylate is widened, thereby reducing its flow rate, having better adhesion and faster curing rate during the bonding process, and being easier to cure and form.
[0031] According to some embodiments of the present application, the method for preparing the modified vinyl acetate resin comprises:
[0032] Add 20-40 parts of hydroxypropyl methylcellulose and 150-200 parts of vinyl acetate by weight, stir at a temperature of 75-85°C, mix evenly, add 3-6 parts of isopropyl triisostearyl titanate, 5-10 parts of sodium dodecyl sulfonate, and 1-2 parts of silicone oil in sequence, disperse evenly, add dropwise 0.3-0.5 parts of 0.3% by mass potassium persulfate solution, react at 85-95°C for 40-60 minutes, and obtain modified vinyl acetate resin.
[0033] By modifying vinyl acetate, the fluidity and adhesion of the resin matrix can be improved, the stability of the adhesive can be improved, and after curing, it will not be easy to crack at low temperatures and will not melt at high temperatures.
[0034] According to some embodiments of the present application, the weight ratio of the acid solution to 3-aminopropyltriethoxysilane in step (3) is 1:(2-3).
[0035] According to some embodiments of the present application, the average diameter of the ultrafine glass fiber in step (2) is 2.5 μm-5 μm; further, the average diameter of the ultrafine glass fiber in step (2) is 3 μm-4 μm. For example, the average diameter of the ultrafine glass fiber in step (2) is 3.6 μm.
[0036] According to some embodiments of the present application, the average length of the ultrafine glass fibers in step (2) is 0.5 cm-2 cm.
[0037] According to some embodiments of the present application, the rotation speed of the drum in step (2) is 3500r / min-4000r / min.
[0038] According to some embodiments of the present application, the spraying thickness in step (4) is 0.1-0.5 mm. When the thickness of the adhesive spraying is controlled within the above range, the comprehensive performance of the ultrafine centrifugal glass wool produced is better. If the thickness of the adhesive spraying is too large, the fiber nodes contain a large amount of glue, which can easily cause the ultrafine glass fiber wool to become compacted, have lower fluffiness, and have higher hardness.
[0039] According to some embodiments of the present application, the low viscosity solvent in step (4) is selected from one of acetone, ethanol, and methyl ethyl ketone.
[0040] According to some embodiments of the present application, the auxiliary agent in step (4) is triethyl phosphate. The binder is a resin material, and its flammable property has a great influence on the flame retardant properties of the ultrafine glass fiber wool. Triethyl phosphate has extremely low viscosity and a high phosphorus content, and has a good flame retardant effect, which can improve the flame retardancy of the binder, thereby improving the overall flame retardancy of the ultrafine centrifugal glass wool.
[0041] In a second aspect, the embodiments of the present application provide ultrafine centrifugal glass wool prepared by the above-mentioned preparation method.
[0042] An ultrafine centrifugal glass wool according to an embodiment of the present application has at least the following beneficial effects:
[0043] The ultrafine centrifugal glass fiber wool of the present application uses epoxy resin and modified polymethyl methacrylate polymer material as an adhesive, and is bonded with ultrafine glass fibers produced by a centrifugal method. The ultrafine centrifugal glass wool produced maintains sound insulation and corrosion resistance while further improving wear resistance and toughness, and reducing the generation of ultrafine glass wool fragments and fibers. DETAILED DESCRIPTION
[0044] To make the purpose, technical solution and advantages of the present application clearer, the following will be further described in detail in conjunction with specific embodiments. The embodiments described here are only part of the embodiments of the present application and cannot be understood as limiting the scope of protection of the present application.
[0045] Example 1
[0046] Preparation of ultrafine centrifugal glass wool: Select the raw materials of glass raw materials by weight: 58 parts of silicon dioxide, 2.5 parts of titanium nitride with an average particle size of 750nm, 1.5 parts of aluminum oxide, 4 parts of calcium oxide, 5 parts of boron oxide, 2.5 parts of magnesium oxide, 4 parts of sodium oxide, 4 parts of lithium oxide, 2.5 parts of barium oxide, 2.5 parts of scandium oxide, and 2.5 parts of manganese oxide; wherein the binder is a mixture of modified polymethyl methacrylate resin, modified vinyl acetate resin and tetraglycidylamine epoxy resin AG-80 with a solid content of 90% in a weight ratio of 4:1:3; the weight ratio of the binder to acetone and triethyl phosphate is 1:3:2; the acid solution is a mixture of hydrochloric acid and hydrofluoric acid in a weight ratio of 2.5:1; the surface of the titanium nitride is plated with a nickel layer;
[0047] (1) Put the glass raw materials into a high-temperature kiln at 1500°C to melt into glass slurry;
[0048] (2) The molten slurry enters the fiberizing machine, and the rotation speed of the drum is 3800r / min. The molten slurry is spun through the small holes on the drum into ultra-fine glass fibers with an average diameter of 3.6μm and an average length of 1cm;
[0049] (3) mixing an acid solution and 3-aminopropyltriethoxysilane in a weight ratio of 1:2 to form a pretreatment solution; immersing the glass fiber in the pretreatment solution, subjecting the glass fiber to ultrasonic treatment for 8 minutes to fully immerse the glass fiber, and then spraying saturated lime water on the surface of the glass fiber to obtain a pretreated glass fiber;
[0050] (4) Evenly mix the binder with acetone and triethyl phosphate, and spray evenly onto the surface of the pretreated glass fiber with a spraying thickness of 0.3 mm to bond the glass fiber into shape;
[0051] (5) Send the bonded glass fiber into a curing furnace for heating to solidify the binder and solidify the fiber into shape;
[0052] The preparation method of the modified polymethyl methacrylate resin is as follows: 45 parts of polymethyl methacrylate resin, 0.5 parts of dicumyl peroxide and 1.5 parts of trihydroxypropane triacrylate are uniformly mixed in a high-speed mixer according to weight parts, added into a torque rheometer with a rotation speed of 60 r / min, and reacted at 165° C. for 2.5 hours to obtain the modified polymethyl methacrylate resin;
[0053] The preparation method of the modified vinyl acetate resin is as follows: 30 parts of hydroxypropyl methylcellulose and 180 parts of vinyl acetate are added by weight, stirred at a temperature of 80°C, mixed evenly, 5 parts of isopropyl triisostearyl titanate, 7 parts of sodium dodecyl sulfate, and 1.5 parts of silicone oil are added in sequence, dispersed evenly, 0.4 parts of 0.3% by mass potassium persulfate solution is added dropwise, and the mixture is reacted at 90°C for 50 minutes to obtain the modified vinyl acetate resin.
[0054] Example 2
[0055] Preparation of ultrafine centrifugal glass wool: Select the raw materials of glass raw materials by weight: 60 parts of silicon dioxide, 3 parts of titanium nitride with an average particle size of 1000nm, 1 part of aluminum oxide, 5 parts of calcium oxide, 4 parts of boron oxide, 3 parts of magnesium oxide, 2 parts of sodium oxide, 5 parts of lithium oxide, 2 parts of barium oxide, 3 parts of scandium oxide, and 2 parts of manganese oxide; wherein the binder is a mixture of modified polymethyl methacrylate resin, modified vinyl acetate resin and tetraglycidylamine epoxy resin AG-80 with a solid content of 95% in a weight ratio of 3:1:3; the weight ratio of the binder to ethanol and triethyl phosphate is 1:2:2; the acid solution is a mixture of hydrochloric acid and hydrofluoric acid in a weight ratio of 3:1; the surface of the titanium nitride is plated with a nickel layer;
[0056] (1) Put the glass raw materials into a high-temperature kiln at 1400°C to melt into glass slurry;
[0057] (2) The molten slurry enters the fiberizing machine, and the rotation speed of the drum is 3500r / min. The molten slurry is spun through the small holes on the drum into ultra-fine glass fibers with an average diameter of 5μm and an average length of 0.5cm;
[0058] (3) mixing an acid solution and 3-aminopropyltriethoxysilane in a weight ratio of 1:3 to form a pretreatment solution; immersing the glass fiber in the pretreatment solution, performing ultrasonic treatment for 10 minutes to fully immerse the glass fiber, and then spraying saturated lime water on the surface of the glass fiber to obtain a pretreated glass fiber;
[0059] (4) Evenly mix the binder with ethanol and triethyl phosphate, and spray it evenly on the surface of the pretreated glass fiber with a spraying thickness of 0.1 mm to bond the glass fiber into shape;
[0060] (5) Send the bonded glass fiber into a curing furnace for heating to solidify the binder and solidify the fiber into shape;
[0061] The preparation method of the modified polymethyl methacrylate resin is as follows: 50 parts of polymethyl methacrylate resin, 0.4 parts of dicumyl peroxide and 2 parts of trihydroxypropane triacrylate are mixed uniformly in a high-speed mixer according to weight parts, added into a torque rheometer with a rotation speed of 60 r / min, and reacted at 165° C. for 2 hours to obtain the modified polymethyl methacrylate resin;
[0062] The preparation method of the modified vinyl acetate resin is as follows: 40 parts of hydroxypropyl methylcellulose and 150 parts of vinyl acetate are added by weight, stirred at a temperature of 85°C, mixed evenly, 3 parts of isopropyl triisostearyl titanate, 10 parts of sodium dodecyl sulfate, and 1 part of silicone oil are added in sequence, dispersed evenly, 0.5 parts of 0.3% by mass potassium persulfate solution are added dropwise, and the mixture is reacted at 85°C for 60 minutes to obtain the modified vinyl acetate resin.
[0063] Example 3
[0064] Preparation of ultrafine centrifugal glass wool: Select the raw materials of glass raw materials by weight: 55 parts of silicon dioxide, 2 parts of titanium nitride with an average particle size of 500nm, 2 parts of aluminum oxide, 3 parts of calcium oxide, 6 parts of boron oxide, 2 parts of magnesium oxide, 5 parts of sodium oxide, 3 parts of lithium oxide, 3 parts of barium oxide, 2 parts of scandium oxide, and 3 parts of manganese oxide; wherein the binder is a mixture of modified polymethyl methacrylate resin, modified vinyl acetate resin and tetraglycidylamine epoxy resin AG-80 with a solid content of 85% in a weight ratio of 5:1:2; the weight ratio of the binder to methyl ethyl ketone and triethyl phosphate is 1:5:1; the acid solution is a mixture of hydrochloric acid and hydrofluoric acid in a weight ratio of 2:1; the surface of the titanium nitride is plated with a nickel layer;
[0065] (1) Put the glass raw materials into a high-temperature kiln at 1600°C to melt into glass slurry;
[0066] (2) The molten slurry enters the fiberizing machine, and the rotation speed of the drum is 4000r / min. The molten slurry is spun through the small holes on the drum into ultra-fine glass fibers with an average diameter of 2.5μm and an average length of 2cm;
[0067] (3) mixing an acid solution and 3-aminopropyltriethoxysilane in a weight ratio of 1:2 to form a pretreatment solution; immersing the glass fiber in the pretreatment solution, performing ultrasonic treatment for 5 minutes to fully immerse the glass fiber, and then spraying saturated lime water on the surface of the glass fiber to obtain a pretreated glass fiber;
[0068] (4) Evenly mix the binder with methyl ethyl ketone and triethyl phosphate, and spray evenly onto the surface of the pretreated glass fiber with a spraying thickness of 0.5 mm to bond the glass fiber into shape;
[0069] (5) Send the bonded glass fiber into a curing furnace for heating to solidify the binder and solidify the fiber into shape;
[0070] The preparation method of the modified polymethyl methacrylate resin is as follows: 40 parts of polymethyl methacrylate resin, 0.6 parts of dicumyl peroxide and 1 part of trihydroxypropane triacrylate are mixed uniformly in a high-speed mixer according to weight parts, added into a torque rheometer with a rotation speed of 60 r / min, and reacted at 165° C. for 3 hours to obtain the modified polymethyl methacrylate resin;
[0071] The preparation method of the modified vinyl acetate resin is as follows: 20 parts of hydroxypropyl methylcellulose and 200 parts of vinyl acetate are added by weight, stirred at a temperature of 75°C, mixed evenly, 6 parts of isopropyl triisostearyl titanate, 5 parts of sodium dodecyl sulfate, and 2 parts of silicone oil are added in sequence, dispersed evenly, 0.3 parts of 0.3% by mass potassium persulfate solution is added dropwise, and the mixture is reacted at 95°C for 40 minutes to obtain the modified vinyl acetate resin.
[0072] Example 4
[0073] Preparation of ultrafine centrifugal glass wool: Select the raw materials of glass raw materials by weight: 57 parts of silicon dioxide, 2.5 parts of titanium nitride with an average particle size of 700nm, 1 part of aluminum oxide, 4 parts of calcium oxide, 5 parts of boron oxide, 2 parts of magnesium oxide, 3 parts of sodium oxide, 3 parts of lithium oxide, 2 parts of barium oxide, 2 parts of scandium oxide, and 3 parts of manganese oxide; wherein the binder is a mixture of modified polymethyl methacrylate resin, modified vinyl acetate resin and tetraglycidylamine epoxy resin AG-80 with a solid content of 90% in a weight ratio of 3:1:2; the weight ratio of the binder to acetone and triethyl phosphate is 1:3:2; the acid solution is a mixture of hydrochloric acid and hydrofluoric acid in a weight ratio of 3:1; the surface of the titanium nitride is plated with a nickel layer;
[0074] (1) Put the glass raw materials into a high-temperature kiln at 1500°C to melt into glass slurry;
[0075] (2) The molten slurry enters the fiberizing machine, and the rotation speed of the drum is 3700r / min. The molten slurry is spun through the small holes on the drum into ultra-fine glass fibers with an average diameter of 4μm and an average length of 1.5cm;
[0076] (3) mixing an acid solution and 3-aminopropyltriethoxysilane in a weight ratio of 1:2 to form a pretreatment solution; immersing the glass fiber in the pretreatment solution, subjecting the glass fiber to ultrasonic treatment for 7 minutes to fully immerse the glass fiber, and then spraying saturated lime water on the surface of the glass fiber to obtain a pretreated glass fiber;
[0077] (4) Evenly mix the binder with acetone and triethyl phosphate, and spray evenly onto the surface of the pretreated glass fiber with a spraying thickness of 0.3 mm to bond the glass fiber into shape;
[0078] (5) Send the bonded glass fiber into a curing furnace for heating to solidify the binder and solidify the fiber into shape;
[0079] The preparation method of the modified polymethyl methacrylate resin is as follows: 45 parts of polymethyl methacrylate resin, 0.5 parts of dicumyl peroxide and 1.5 parts of trihydroxypropane triacrylate are uniformly mixed in a high-speed mixer according to weight parts, added into a torque rheometer with a rotation speed of 60 r / min, and reacted at 165° C. for 2.5 hours to obtain the modified polymethyl methacrylate resin;
[0080] The preparation method of the modified vinyl acetate resin is as follows: 35 parts of hydroxypropyl methylcellulose and 170 parts of vinyl acetate are added by weight, stirred at a temperature of 82°C, mixed evenly, 4 parts of isopropyl triisostearyl titanate, 6 parts of sodium dodecyl sulfate, and 1 part of silicone oil are added in sequence, dispersed evenly, 0.4 parts of 0.3% by mass potassium persulfate solution are added dropwise, and the mixture is reacted at 92°C for 45 minutes to obtain the modified vinyl acetate resin.
[0081] Comparative Example 1
[0082] Preparation of ultrafine centrifugal glass wool: Select the raw materials of glass raw materials by weight: 58 parts of silicon dioxide, 2.5 parts of titanium nitride with an average particle size of 750nm, 1.5 parts of aluminum oxide, 4 parts of calcium oxide, 5 parts of boron oxide, 2.5 parts of magnesium oxide, 4 parts of sodium oxide, 4 parts of lithium oxide, 2.5 parts of barium oxide, 2.5 parts of scandium oxide, and 2.5 parts of manganese oxide; wherein the binder is a mixture of polymethyl methacrylate resin, modified vinyl acetate resin and tetraglycidylamine epoxy resin AG-80 with a solid content of 90% in a weight ratio of 4:1:3; the weight ratio of the binder to acetone and triethyl phosphate is 1:3:2; the acid solution is a mixture of hydrochloric acid and hydrofluoric acid in a weight ratio of 2.5:1; the surface of the titanium nitride is plated with a nickel layer;
[0083] (1) Put the glass raw materials into a high-temperature kiln at 1500°C to melt into glass slurry;
[0084] (2) The molten slurry enters the fiberizing machine, and the rotation speed of the drum is 3800r / min. The molten slurry is spun through the small holes on the drum into ultra-fine glass fibers with an average diameter of 3.6μm and an average length of 1cm;
[0085] (3) mixing an acid solution and 3-aminopropyltriethoxysilane in a weight ratio of 1:2 to form a pretreatment solution; immersing the glass fiber in the pretreatment solution, subjecting the glass fiber to ultrasonic treatment for 8 minutes to fully immerse the glass fiber, and then spraying saturated lime water on the surface of the glass fiber to obtain a pretreated glass fiber;
[0086] (4) Evenly mix the binder with acetone and triethyl phosphate, and spray evenly onto the surface of the pretreated glass fiber with a spraying thickness of 0.3 mm to bond the glass fiber into shape;
[0087] (5) Send the bonded glass fiber into a curing furnace for heating to solidify the binder and solidify the fiber into shape;
[0088] The preparation method of the modified vinyl acetate resin is as follows: 30 parts of hydroxypropyl methylcellulose and 180 parts of vinyl acetate are added by weight, stirred at a temperature of 80°C, mixed evenly, 5 parts of isopropyl triisostearyl titanate, 7 parts of sodium dodecyl sulfate, and 1.5 parts of silicone oil are added in sequence, dispersed evenly, 0.4 parts of 0.3% by mass potassium persulfate solution is added dropwise, and the mixture is reacted at 90°C for 50 minutes to obtain the modified vinyl acetate resin.
[0089] Comparative Example 2
[0090] Preparation of ultrafine centrifugal glass wool: Select the raw materials of glass raw materials by weight: 58 parts of silicon dioxide, 2.5 parts of titanium nitride with an average particle size of 750nm, 1.5 parts of aluminum oxide, 4 parts of calcium oxide, 5 parts of boron oxide, 2.5 parts of magnesium oxide, 4 parts of sodium oxide, 4 parts of lithium oxide, 2.5 parts of barium oxide, 2.5 parts of scandium oxide, and 2.5 parts of manganese oxide; wherein the binder is modified polymethyl methacrylate resin; the weight ratio of the binder to acetone and triethyl phosphate is 1:3:2; the acid solution is a mixture of hydrochloric acid and hydrofluoric acid in a weight ratio of 2.5:1; the surface of the titanium nitride is plated with a nickel layer;
[0091] (1) Put the glass raw materials into a high-temperature kiln at 1500°C to melt into glass slurry;
[0092] (2) The molten slurry enters the fiberizing machine, and the rotation speed of the drum is 3800r / min. The molten slurry is spun through the small holes on the drum into ultra-fine glass fibers with an average diameter of 3.6μm and an average length of 1cm;
[0093] (3) mixing an acid solution and 3-aminopropyltriethoxysilane in a weight ratio of 1:2 to form a pretreatment solution; immersing the glass fiber in the pretreatment solution, subjecting the glass fiber to ultrasonic treatment for 8 minutes to fully immerse the glass fiber, and then spraying saturated lime water on the surface of the glass fiber to obtain a pretreated glass fiber;
[0094] (4) Evenly mix the binder with acetone and triethyl phosphate, and spray evenly onto the surface of the pretreated glass fiber with a spraying thickness of 0.3 mm to bond the glass fiber into shape;
[0095] (5) Send the bonded glass fiber into a curing furnace for heating to solidify the binder and solidify the fiber into shape;
[0096] Among them, the preparation method of the modified polymethyl methacrylate resin is: 45 parts of polymethyl methacrylate resin, 0.5 parts of dicumyl peroxide and 1.5 parts of trihydroxypropane triacrylate are mixed uniformly in a high-speed mixer according to weight parts, added into a torque rheometer with a rotation speed of 60r / min, and reacted at 165°C for 2.5h to obtain the modified polymethyl methacrylate resin.
[0097] Comparative Example 3
[0098] Preparation of ultrafine centrifugal glass wool: Select the raw materials of glass raw materials by weight: 58 parts of silicon dioxide, 1.5 parts of aluminum oxide, 4 parts of calcium oxide, 5 parts of boron oxide, 2.5 parts of magnesium oxide, 4 parts of sodium oxide, 4 parts of lithium oxide, 2.5 parts of barium oxide, 2.5 parts of scandium oxide, and 2.5 parts of manganese oxide; wherein the binder is a mixture of modified polymethyl methacrylate resin, modified vinyl acetate resin and tetraglycidylamine epoxy resin AG-80 with a solid content of 90% in a weight ratio of 4:1:3; the weight ratio of the binder to acetone and triethyl phosphate is 1:3:2; the acid solution is a mixture of hydrochloric acid and hydrofluoric acid in a weight ratio of 2.5:1;
[0099] (1) Put the glass raw materials into a high-temperature kiln at 1500°C to melt into glass slurry;
[0100] (2) The molten slurry enters the fiberizing machine, and the rotation speed of the drum is 3800r / min. The molten slurry is spun through the small holes on the drum into ultra-fine glass fibers with an average diameter of 3.6μm and an average length of 1cm;
[0101] (3) mixing an acid solution and 3-aminopropyltriethoxysilane in a weight ratio of 1:2 to form a pretreatment solution; immersing the glass fiber in the pretreatment solution, subjecting the glass fiber to ultrasonic treatment for 8 minutes to fully immerse the glass fiber, and then spraying saturated lime water on the surface of the glass fiber to obtain a pretreated glass fiber;
[0102] (4) Evenly mix the binder with acetone and triethyl phosphate, and spray evenly onto the surface of the pretreated glass fiber with a spraying thickness of 0.3 mm to bond the glass fiber into shape;
[0103] (5) Send the bonded glass fiber into a curing furnace for heating to solidify the binder and solidify the fiber into shape;
[0104] The preparation method of the modified polymethyl methacrylate resin is as follows: 45 parts of polymethyl methacrylate resin, 0.5 parts of dicumyl peroxide and 1.5 parts of trihydroxypropane triacrylate are uniformly mixed in a high-speed mixer according to weight parts, added into a torque rheometer with a rotation speed of 60 r / min, and reacted at 165° C. for 2.5 hours to obtain the modified polymethyl methacrylate resin;
[0105] The preparation method of the modified vinyl acetate resin is as follows: 30 parts of hydroxypropyl methylcellulose and 180 parts of vinyl acetate are added by weight, stirred at a temperature of 80°C, mixed evenly, 5 parts of isopropyl triisostearyl titanate, 7 parts of sodium dodecyl sulfate, and 1.5 parts of silicone oil are added in sequence, dispersed evenly, 0.4 parts of 0.3% by mass potassium persulfate solution is added dropwise, and the mixture is reacted at 90°C for 50 minutes to obtain the modified vinyl acetate resin.
[0106] Experimental example
[0107] The ultrafine centrifugal glass wool prepared in Examples 1-4 and Comparative Examples 1-3 was tested for bending failure load, friction resistance, corrosion resistance, sound insulation, and flame retardancy, respectively, and the test methods are as follows:
[0108] The bending failure load is tested according to the standard of GB / T 13350-2017.
[0109] The friction resistance is tested according to the standard of GB / T 1768-2006.
[0110] The sound insulation performance is tested according to the standard of JC / T 2703-2022.
[0111] The flame retardant grade is tested according to the standard of GB 8624-2012.
[0112] The corrosion resistance is tested according to the standard of GB / T 3857-2017. If the surface gloss, color, obvious softening or hardening, cracks, delamination, fiber exposure, swelling and other appearance of the sample remain unchanged, the corrosion resistance is recorded as Grade 1 (corrosion resistant); if at least one of the surface gloss, color, obvious softening or hardening, cracks, delamination, fiber exposure, swelling and other appearance of the sample changes slightly, the corrosion resistance is recorded as Grade 2 (still corrosion resistant); if at least one of the surface gloss, color, obvious softening or hardening, cracks, delamination, fiber exposure, swelling and other appearance of the sample changes significantly, the corrosion resistance is recorded as Grade 3 (not corrosion resistant).
[0113] The test data is shown in Table 1 below:
[0114] Table 1
[0115] Test items Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Comparative Example 3 Bending failure load (N) 185 183 182 184 148 104 53 Friction resistance (mg) 11 12 13 12 26 33 39 Corrosion resistance Level 1 Level 1 Level 1 Level 1 Level 2 Level 2 Level 1 Sound insulation (noise reduction coefficient NRC) 0.85 0.88 0.86 0.86 0.64 0.58 0.62 Flame retardant grade B1 B1 B1 B1 B1 B1 B1
[0116] It can be seen from Table 1 that the ultrafine centrifugal glass wool prepared in Examples 1-4 of the present application has excellent toughness and abrasion resistance, and also has good corrosion resistance, sound insulation and flame retardancy.
[0117] The polymethyl methacrylate resin in the preparation raw materials of Comparative Example 1 has not been modified, and the rest is the same as Example 1. The ultrafine centrifugal glass wool prepared in Comparative Example 1 has poor toughness and abrasion resistance, and its corrosion resistance also decreases. The sound insulation performance is also not as good as the ultrafine centrifugal glass wool in Example 1, which shows that the modification of the polymethyl methacrylate resin in this application can make the curing process more sufficient and improve the comprehensive performance of the ultrafine centrifugal glass wool.
[0118] The preparation raw materials of Comparative Example 2 do not contain modified vinyl acetate resin and tetraglycidylamine type epoxy resin AG-80, and the rest are the same as Example 1. The ultrafine centrifugal glass wool prepared in Comparative Example 2 has poor toughness and abrasion resistance, and its corrosion resistance also decreases. The sound insulation performance is also not as good as the ultrafine centrifugal glass wool of Example 1, which shows that the amino epoxy resin can react chemically with a variety of functional groups to form chemical bonds, thereby enhancing the bonding force between the binder and the glass fiber, thereby improving the overall strength and stability of the glass fiber wool, and at the same time improving the high temperature resistance and corrosion resistance of the binder.
[0119] No titanium nitride was added to the raw materials for the preparation of Comparative Example 3, and the rest were the same as Example 1. The ultrafine centrifugal glass wool prepared in Comparative Example 3 had significantly poorer toughness and abrasion resistance, and its sound insulation performance was also inferior to that of the ultrafine centrifugal glass wool in Example 1, indicating that the addition of titanium nitride can help form a more uniform and dense fiber structure, thereby improving the overall wear resistance and toughness.
[0120] Although the embodiments of the present application have been shown and described, those skilled in the art will appreciate that various changes, modifications, substitutions or variations may be made to the embodiments without departing from the principles and purpose of the present application, and that the technical solutions after these changes, modifications, substitutions or variations will fall within the scope of protection of the present application.
Claims
1. A method for preparing ultrafine centrifugal glass wool, characterized in that: The following steps are involved: (1) Put the glass raw materials into a high-temperature kiln at 1400-1600℃ and melt them into glass slurry; (2) The molten slurry enters the fiberizing machine and is thrown into ultra-fine glass fibers through the small holes on the drum; (3) mixing an acid solution and 3-aminopropyltriethoxysilane to form a pretreatment solution; immersing the ultrafine glass fiber in the pretreatment solution, subjecting the glass fiber to ultrasonic treatment for 5-10 minutes to fully immerse the glass fiber, and then spraying saturated lime water on the surface of the glass fiber to obtain the pretreated glass fiber; (4) Evenly mix the binder with the low-viscosity solvent and the additive, and evenly spray it onto the surface of the pretreated glass fiber to bond the glass fiber into shape; (5) Send the bonded glass fiber into a curing furnace for heating to solidify the binder and solidify the fiber into shape; Wherein, the acid solution in step (3) is prepared by mixing hydrochloric acid and hydrofluoric acid in a weight ratio of (2-3):1; The adhesive in step (4) is prepared by mixing modified polymethyl methacrylate resin, modified vinyl acetate resin and epoxy resin in a weight ratio of (3-5):1:(2-3); Step (1) The glass raw material is composed of the following raw materials in parts by weight: 55-60 parts of silicon dioxide, 2-3 parts of titanium nitride, 1-2 parts of aluminum oxide, 3-5 parts of calcium oxide, 4-6 parts of boron oxide, 2-3 parts of magnesium oxide, 2-5 parts of sodium oxide, 3-5 parts of lithium oxide, 2-3 parts of barium oxide, 2-3 parts of scandium oxide, and 2-3 parts of manganese oxide; In step (4), the weight ratio of the binder to the low-viscosity solvent and the auxiliary agent is 1:(2-5):(1-2).
2. The method for preparing ultrafine centrifugal glass wool according to claim 1, characterized in that: The solid content of the epoxy resin is 85-95%, and / or the epoxy resin contains an active monomer with an amine group.
3. The method for preparing ultrafine centrifugal glass wool according to claim 1, characterized in that: The preparation method of the modified polymethyl methacrylate resin comprises: 40-50 parts of polymethyl methacrylate resin, 0.4-0.6 parts of dicumyl peroxide and 1-2 parts of trihydroxypropane triacrylate are mixed uniformly in a high-speed mixer according to weight parts, added into a torque rheometer with a rotation speed of 60 r / min, and reacted at 165° C. for 2-3 hours to obtain modified polymethyl methacrylate resin.
4. The method for preparing ultrafine centrifugal glass wool according to claim 1, characterized in that: The preparation method of the modified vinyl acetate resin comprises: Add 20-40 parts of hydroxypropyl methylcellulose and 150-200 parts of vinyl acetate by weight, stir at a temperature of 75-85°C, mix evenly, add 3-6 parts of isopropyl triisostearyl titanate, 5-10 parts of sodium dodecyl sulfonate, and 1-2 parts of silicone oil in sequence, disperse evenly, add dropwise 0.3-0.5 parts of 0.3% by mass potassium persulfate solution, react at 85-95°C for 40-60 minutes, and obtain modified vinyl acetate resin.
5. The method for preparing ultrafine centrifugal glass wool according to claim 1, characterized in that: The low viscosity solvent in step (4) is selected from acetone, ethanol, and methyl ethyl ketone.
6. The method for preparing ultrafine centrifugal glass wool according to claim 1, characterized in that: The auxiliary agent in step (4) is triethyl phosphate.
7. The method for preparing ultrafine centrifugal glass wool according to claim 1, characterized in that: The spraying thickness in step (4) is 0.1-0.5 mm.
8. The method for preparing ultrafine centrifugal glass wool according to claim 1, characterized in that: The average diameter of the ultrafine glass fibers in step (2) is 2.5 μm-5 μm, and / or the average length of the ultrafine glass fibers in step (2) is 0.5 cm-2 cm.
9. The method for preparing ultrafine centrifugal glass wool according to claim 1, characterized in that: The rotation speed of the drum in step (2) is 3500r / min-4000r / min.
10. Ultrafine centrifugal glass wool produced by the method for preparing ultrafine centrifugal glass wool as claimed in any one of claims 1 to 9.
Citation Information
Patent Citations
Surface treatment method for basalt fibre
CN101125738A
High-strength thermal-insulation sound-insulation superfine glass fiber cotton for aviation and preparation method thereof
CN106966583A